African Canadian leadership: Continuity, transition, and transformation - Kitossa, Tamari; Lawson, Erica; Howard, Philip S. S. (University of Toronto Press, 2019)
Challenging the myth of African Canadian leadership "in crisis," this book opens a broad vista of inquiry into the many and dynamic ways leadership practices occur in Black Canadian communities. Exploring topics including Black women’s contributions to African Canadian communities, the Black Lives Matter movement, Black LGBTQ, HIV/AIDS advocacy, motherhood and grieving, mentoring, and anti-racism, contributors appraise the complex history and contemporary reality of blackness and leadership in Canada. With Canada as a complex site of Black diasporas, contributors offer an account of multiple forms of leadership and suggest that through surveillance and disruption, practices of self-determined Black leadership are incompatible with, and threatening to, White "structures" of power in Canada. As a whole, African Canadian Leadership offers perspectives that are complex, non-aligned, and in critical conversation about class, gender, sexuality, and the politics of African Canadian communities.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; discours dominant; fem3300; féminisme afroaméricain; histoire et politique; identités LGBTQIA2+; maternité; militance; premier cycle; racisme; régions géographiques; systèmes d'oppressions; thématiques